Web-Based E-commerce Application at Narmada Furniture Store - Linda Norhan (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2021)
Narmada Furniture Store is a store engaged in the sale of household furniture items such as tables, chairs, mattresses, cabinets, and others. At the Narmada Furniture Store, the sales system used today is a conventional system, namely the buyer must come directly to the store to see the products offered. At this time the Narmada Furniture Store does not yet have an e-commerce application, so it is difficult to offer products to consumers who are outside the city. In addition, it also results in consumer ignorance of the existence of Narmada Furniture Stores. The selling process of the Narmada Furniture Store is only carried out if there are consumers who come to the store, while many consumers both in Cirebon and outside the city of Cirebon cannot come or do not know the existence of the Narmada Furniture Store. In analyzing the system, a description of the current system procedures is carried out, so that the system's strengths and weaknesses can be evaluated. In the process of making the system begins with the system analysis stage. Then the process modeling is described using flowmaps, context diagrams, data flow diagrams (Data Flow Diagrams) and Entity Relationship Diagrams (ERD). After the analysis stage is complete, it is continued with the design stage, by making table designs, table relations, program structures, program input and output designs. With this e-commerce application, it is expected to make it easier for consumers to obtain information about product specifications offered by Narmada Furniture Stores. Make it easy for Narmada Furniture Stores in selling their products to consumers who are inside and outside the city of Cirebon. Consumers can find out where the Narmada Furniture store is by using this e-commerce application service and can buy products without having to come to the store. And make it easier for leaders to make decisions based on the output of sales transaction reports and sales charts per month.